1988
DOI: 10.1161/01.hyp.12.1.26
|View full text |Cite
|
Sign up to set email alerts
|

Intralymphocytic sodium and free calcium and plasma renin in essential hypertension.

Abstract: SUMMARY Intraceilular sodium, potassium, and free calcium concentrations were investigated in lymphocytes of 30 patients with essential hypertension and 30 normotensive controls. All subjects were placed on a diet containing 8 to 10 g of sodium chloride per day. Lymphocyte sodium concentration was higher in hypertensive patients than in normotensive controls (19.8 ± 1.8 vs 18.4 ± 1.8 mmol/kg wet weight; p < 0.01), whereas lymphocyte potassium concentration was similar in both groups. Lymphocyte free calcium co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

1990
1990
1999
1999

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 34 publications
2
11
0
Order By: Relevance
“…Although these investigators showed higher levels of lymphocyte [Ca 2ϩ ] c and [Na ϩ ] c in patients with essential hypertension than in normotensive controls, they did not find correlations for the levels of these ions with blood pressure when blood pressure was evaluated as a continuously distributed variable. 19,20,29 The present study and our previous work 17 have confirmed the lack of correlation between the resting [Ca 2ϩ ] c in lymphocytes and blood pressure. However, we did show a strong correlation between the [Na ϩ ] c in lymphocytes and blood pressure in men but not in women.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Although these investigators showed higher levels of lymphocyte [Ca 2ϩ ] c and [Na ϩ ] c in patients with essential hypertension than in normotensive controls, they did not find correlations for the levels of these ions with blood pressure when blood pressure was evaluated as a continuously distributed variable. 19,20,29 The present study and our previous work 17 have confirmed the lack of correlation between the resting [Ca 2ϩ ] c in lymphocytes and blood pressure. However, we did show a strong correlation between the [Na ϩ ] c in lymphocytes and blood pressure in men but not in women.…”
Section: Resultssupporting
confidence: 88%
“…Oshima et al 20,29 have demonstrated a strong correlation between [Na ϩ ] c (measured by flame photometry) and [Ca 2ϩ ] c in lymphocytes from hypertensive and normotensive subjects. Although these investigators showed higher levels of lymphocyte [Ca 2ϩ ] c and [Na ϩ ] c in patients with essential hypertension than in normotensive controls, they did not find correlations for the levels of these ions with blood pressure when blood pressure was evaluated as a continuously distributed variable.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…In the presence of 1 mM external calcium, thrombin-induced [Ca 2+ ]j was significantly higher in SHR compared with WKY rats (491.4+31.6 vs. 377.5+21.7 nM,/?<0.002), and there was no overlap in the distribution between groups. In the absence of external calcium, we found a small but significant difference in the peak [ ]j in blood cells has a disadvantage in interpretation of data because hypertensive patients have heterogeneity in several factors such as renin status, 20 blood pressure level, 6 age, 9 and salt intake, 11 ' 21 each of which may influence intracellular cation characteristics and are difficult to control precisely. However, the human data, in fact, demonstrate consistently elevated [Ca 2+ ]j in platelets from hypertensive subjects, whereas the status of platelet [Ca 2+ ] ; in SHR is controversial.…”
Section: Resultsmentioning
confidence: 84%
“…1 - 3 Blood cells frequently have been used for the analysis of cellular calcium metabolism because they are readily available and easy to handle. Thus, there have been many reports that basal intracellular free calcium ([Ca 2+ ]|) is increased in lymphocytes 4 - 6 and platelets 5 -7 -11 of patients with essential hypertension and spontaneously hypertensive rats (SHR) in comparison with their respective normotensive controls. However, concern has been raised about using circulating blood cells 12 because of their exposure to the mechanical shear forces in the circulatory system that could alter cellular calcium metabolism or cell function.…”
mentioning
confidence: 99%